The effect of perceived transformational leadership style on employee engagement: The mediating effect of leader's emotional intelligence - Marwan Milhem; Habsah Muda; Khalil Ahmed (Foundations of Management, 2019)
Employee engagement has been at the center of attention for human resource personnel and researchers who stated that employee engagement can be a key driver of an organization's business success. Many researchers have found in recent researches that a transformational leadership style has a beneficial connection with employee engagement. Thus, this study aims to find the causal effect of perceived transformational leadership on employee engagement through the mediating role of leader's emotional intelligence. We analyze the data from a sample of 338 full-time employees working in the ICT sector in Palestine using confirmatory factor analysis (CFA) and structural equation modelling (SEM) to test the hypothesis. Later, the bootstrapping analysis was conducted to confirm the mediation test in this study. The finding shows that transformational leadership style has a significant effect on employee engagement for the mediating role of emotional intelligence. The effect of transforma-tional leadership on employee engagement was found to be completely mediated by leader's emotional intelligence at work. Theoretically, this empirical study contributed to the new knowledge on the unique mediating effects of leader's emotional intelligence in the relationship between transformational leadership and employee engagement in the Middle Eastern Region. Practically, this study has manage-rial implication in the area of organizational management, leadership and human resource management.
Keywords: M1; M10; M12; 650; employee engagement (EE); emotional intelligence (EI); transformational leadership; ex-ploratory factor analysis (EFA); confirmatory factor analysis (CFA); information & communication technology (ICT); structural equation modelling (SEM)